Spiny lobster development: where does successful metamorphosis to the puerulus occur?: a review - Phillips, Bruce; McWilliam, P. (Springer, 2008)
This review re-addresses the question: Where does metamorphosis to the puerulus mainly take place among the shallow-water palinurids? A decade ago we reviewed this ecological question in a paper that focused on phyllosomal development of the western rock lobster, Panulirus cygnus. The main region of occurrence of its metamorphosis was found to be in the slope region beyond the shelf break. Because the puerulus of P. cygnus is a non-feeding stage, it was hypothesised that metamorphosis will not occur until the final phyllosoma has reached some critical, and specific, level of stored energy reserves. For late larval development and successful metamorphosis of P. cygnus, the richest food resources seem to be located in the slope waters adjoining the shelf break off Western Australia. This, like most shelf break areas, is a region of higher zooplankton and micronekton biomass than is usually found further offshore, and is dominated (in winter-spring months) by the warm south-flowing Leeuwin Current. In this new review, distribution and abundance data of final phyllosomas and pueruli are examined from, Panulirusargus, Panulirus cygnus, Panulirus japonicus, Panulirus ornatus and Jasus edwardsii, and where possible, related to features of the satellite imagery of the areas in which they occur. We hypothesise that metamorphosis will occur where the final stages have partaken of sufficient, appropriate nutrition to provide them with a reserve of bioenergetic resources, and this can occur where oceanographic fronts effect greater planktonic productivity and concentrations of food organisms. This may be near the shelf-break, or out to large distances offshore, because of large-scale oceanographic events such as the prevailing current system, its off-shoots, mesoscale eddy fronts, counter-currents, etc. However, we contend that, in terms of population recruitment, metamorphosis in most shallow-water palinurid species occurs mainly in the slope waters adjoining the shelf break of the region to which the species is endemic. Although some final phyllosomas may metamorphose much further offshore, it is unlikely that these pueruli will reach the shore, let alone settle and successfully moult to the juvenile stage. All of the data indicate that successful metamorphosis from the final-stage phyllosoma to the puerulus stage in all species occurs offshore but close to the continental shelf.